A transposição do Rio São Francisco na voz dos diretamente atingidos em Cabrobó (PE) - Andre Tome de Assis (2015)
The "São Francisco River Integration Project Watershed with the Northern Northeast Brazil," or as it is popularly called, the transposition of the São Francisco river, does not claim to solve the historical problem of the drought in the northern Northeast. As the population of a place, realize and live with the changes, and the expectations generated by the transposition? In an attempt to answer this question, the general objective of this thesis is to record, understand, and discuss the voice of farmers directly affected by the implementation, in the municipality of Cabrobó (PE); contrasting the voice of these subjects, with the official discourse of managers of big business. As historical review, other transpositions were also investigated, including those carried out in other countries, such as the Tagus river, in Spain and Portugal, surveyed sandwich doctorate at the University of Coimbra, in the year 2014. The geographical categories place and territory , guided to the cut and understanding of the analyzed space. The phenomenology method, focusing on "Perception" and "Oral History", values the voice of respondents. As a result, it can be said that respondents reported little or no positive expectation regarding the transposition. They said they really need water, but note, by the way the work is being carried out, contempt and disregard for the problems and needs they face. Respondents reported that the work was imposed and there was lack of dialogue; there is fear that they might not come to have access transposed the water and still be expelled or oppressed by other enterprises that can get there. Work on the transposition interfered not only on environmental and economic issues, but the entire social structure, cultural and historic farmers. It indicates that respondents understand where they live and know how to bring answers to several questions. This thesis investigates a time and place of the transposition. It stresses that this project, by its magnitude, you need a continuity in scientific research.